Pengaruh Komposisi Perekat Terhadap Karakteristik Termal Briket Arang Kulit Biji Buah Jarak - Lafose, Maliadin; Balaka, Ridway; Kadir, Kadir (Teknik Mesin Universitas Halu Oleo, 2020)
The fruit grain Bark range is one potential alternative fuel to make briquettes. This research was conducted to know the proximate analysis and the rate ofcombustion of biocharcoal briquettes produced from the bark of the distance.Charcoal fruit beans that have been carbonized distances are further filtered using a sieve of 40 mesh with variations of kanji adhesive Composition 90%: 10%, 80%: 20% and 70%: 30%. Then both materials are mixed and printed into briquette then tested to know the heat value, moisture content, ash content, the content of flying substances, carbon levels and the rate of combustion. Based on the results of analysis obtained from this research if it is reviewed from the proximate analysis is the best fruit seed leather briquette is shown by charcoal briquettes of fruit beans distance and adhesive kanji with composition 90%: 10%, Heat value 6830 cal/GR, water content 8.82%, ash content 4.88%, flying substance content of 13.16% and fixed carbon levels 73.14%. The results of this study showed the difference treatment of composition of the leather charcoal briquette fruit range and adhesive kanji can give effect to the value of heat, moisture content, ash content.The content of flying substances, and fixed carbon levels.Keywords: Fuel, charcoal briquette, adhesive material, leather fruit grain spacing.